Macroporous nanofiber wraps promote axonal regeneration and functional recovery in nerve repair by limiting fibrosis. (1st April 2019) - Sarhane, Karim A.; Ibrahim, Zuhaib; Martin, Russell; Krick, Kellin; Cashman, Christopher R.; Tuffaha, Sami H.; Broyles, Justin M.; Prasad, Nijaguna; Yao, Zhi-Cheng; Cooney, Damon S.; Mi, Ruifa; Lee, WP Andrew; et al.
Graphical abstract: Abstract: Functional outcomes following nerve repair remain suboptimal. Scarring at the repair site is a major impediment to regeneration. A biomaterial scaffold applied around the coaptation site that decreases inflammation holds great potential in reducing scarring, enhancing axonal growth, and improving functional recovery. In this study, we evaluated the effect of a macroporous nanofiber wrap, comprised of nonwoven electrospun poly-ε-caprolactone (PCL), in improving axonal regeneration in a rat sciatic nerve cut and direct repair model. Controls consisted of conventional epineurial repair. We also evaluated our wrap against the commercially available AxoGuard wrap. At five weeks following repair, the nanofiber wrap group showed a significantly decreased intraneural macrophage invasion and collagen deposition at the repair site. This was associated with increased expression of the anti-inflammatory cytokine (IL-10), decreased expression of the pro-inflammatory cytokine (TNF-α), and a decrease in the M1:M2 macrophage phenotype ratio. These findings suggest that this nanofiber wrap, with its unique macroporosity, is modulating the inflammatory response at the repair site by polarizing macrophages towards a pro-regenerative M2 phenotype. Concomitantly, a higher number of regenerated axons was noted. At sixteen weeks, the nanofiber wrap resulted in enhanced functional recovery as demonstrated by electrophysiology, neuromuscular re-innervation, and muscle histology. When compared to the AxoGuard wrap, the nanofiber wrap showed similar inflammation at the repair site and similar nerve morphometric findings, but there was a trend towards a lower overall number of macrophages invading the wrap wall. These results demonstrate favorable outcomes of the macroporous nanofiber wrap in promoting neuroregeneration and functional recovery following nerve repair. Statement of Significance: Electrospun nanofiber scaffolds, with specific fiber and pore sizes, were shown to modulate the immune response and create a regenerative environment. In this paper, we present a macroporous nanofiber wrap, made of poly-ε-caprolactone, to be applied at the coaptation site in primary nerve repair. We show that it regulates the inflammatory response at the repair site and decreases scarring/fibrosis. This results in enhanced axonal regeneration, allowing a higher number of axons to cross the suture line and reach the target muscle in a timely fashion. Functional outcomes are thus improved.